Modulation of Dengue/Zika Virus Pathogenicity by Antibody-Dependent Enhancement and Strategies to Protect Against Enhancement in Zika Virus Infection - Khandia, Rekha; Munjal, Ashok; Dhama, Kuldeep; Karthik, Kumaragurubaran; Tiwari, Ruchi; Malik, Yashpal Singh; Singh, Raj Kumar; Chaicumpa, Wanpen (Frontiers in Immunology, 2018)
Antibody-dependent enhancement (ADE) is a phenomenon in which pre-existing poorly neutralizing antibodies leads to enhanced infection. It is a serious concern with mosquito-borne flaviviruses such as Dengue virus (DENV) and Zika virus (ZIKV). In vitro experimental evidences have indicated the preventive, as well as a pathogenicity-enhancing role, of pre-existing DENV antibodies in ZIKV infections. ADE has been confirmed in DENV but not ZIKV infections. Principally, the Fc region of the anti-DENV antibody binds with the fragment crystallizable gamma receptor (FcγR), and subsequent C1q interactions and immune effector functions are responsible for the ADE. In contrast to normal DENV infections, with ADE in DENV infections, inhibition of STAT1 phosphorylation and a reduction in IRF-1 gene expression, NOS2 levels, and RIG-1 and MDA-5 expression levels occurs. FcγRIIA is the most permissive FcγR for DENV ADE, and under hypoxic conditions, hypoxia-inducible factor 1 alpha transcriptionally enhances expression levels of FcγRIIA, which further enhances ADE. To produce therapeutic antibodies with broad reactivity to different DENV serotypes, as well as to ZIKV, bispecific antibodies, Fc region mutants, modified Fc regions, and anti-idiotypic antibodies may be engineered. An in-depth understanding of the immunological and molecular mechanisms of DENV ADE of ZIKV pathogenicity will be useful for the design of common and safe therapeutics and prophylactics against both viral pathogens. The present review discusses the role of DENV antibodies in modulating DENV/ZIKV pathogenicity/infection and strategies to counter ADE to protect against ZIKA infection.